2010
DOI: 10.1159/000277640
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Polycystic Ovary Syndrome and Related Disorders in Mexican Women

Abstract: Background/Aims: Polycystic ovary syndrome (PCOS) has been found to affect 4–8% of women of reproductive age; however, in Mexican-Americans a prevalence of 12.8% has been reported. This study determines the prevalence of PCOS in a sample of Mexican women. Methods: This prospective cross-sectional study included 150 female Mexican volunteers aged 20–45 years. Menstrual cycles were recorded and hirsutism was graded. Pelvic ultrasound was performed and androgen levels were measured. PCOS was diagnosed by hyperand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
2
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(73 citation statements)
references
References 53 publications
1
61
2
6
Order By: Relevance
“…Although the results of the current study are in concurrence with the previously reported frequency's ranging from 11.2 to 20.9% according to the Rotterdam criteria (18, 26-28), we found lower figures than a prior Turkish cohort study using the AE-PCOS Society criteria (18). Further, data from this study illustrated that the prevalence of insulin resistance and impaired glucose tolerance barely rise in the overall PCOS population (31.7 and 17.8%, respectively) when compared to that reported from another study of Turkish women with PCOS (29). This study has also shown that women with PCOS have a higher prevalence of metabolic syndrome (22.5%) than that consistently reported from the literature, albeit with a varying rate (17,18,28).…”
Section: Discussioncontrasting
confidence: 85%
“…Although the results of the current study are in concurrence with the previously reported frequency's ranging from 11.2 to 20.9% according to the Rotterdam criteria (18, 26-28), we found lower figures than a prior Turkish cohort study using the AE-PCOS Society criteria (18). Further, data from this study illustrated that the prevalence of insulin resistance and impaired glucose tolerance barely rise in the overall PCOS population (31.7 and 17.8%, respectively) when compared to that reported from another study of Turkish women with PCOS (29). This study has also shown that women with PCOS have a higher prevalence of metabolic syndrome (22.5%) than that consistently reported from the literature, albeit with a varying rate (17,18,28).…”
Section: Discussioncontrasting
confidence: 85%
“…El crecimiento de pelo terminal tiene considerable variabilidad étnica y racial (4), el valor del punto de corte debe ser idealmente establecido para la población que se aplica. El punto de corte sugerido para la escala de F-Gm acorde al percentil 95 del presente estudio es de 12 para las mujeres en el rango de edad entre los 15 y 30 años, este punto de corte es superior al percentil 95 reportado en los diferentes estudios incluyendo el estudio chileno (25)(26)(27)(28)(29)(30)(31)(32)(33). Actualmente, muchos médicos e investigadores eligen una puntuación F-Gm igual o mayor a 8 como indicativo del hirsutismo, sin que se excluya la necesidad de evaluar puntos de corte menor cuando existan signos o síntomas clínicos, sugerentes de causas asociadas con riesgo cardiometabólico y perinatal.…”
Section: Discussionunclassified
“…Insulin resistance and obesity are also associated with a number of other metabolic abnormalities observed in PCOS. The prevalence of metabolic syndrome is 2-4 times higher compared to healthy controls [22,23]. Abnormalities of carbohydrate metabolism observed in women with PCOS include an increased frequency of impaired glucose tolerance and of type 2 diabetes mellitus compared to controls matched for age and body mass index (BMI) [24].…”
Section: Szkolenie Podyplomowementioning
confidence: 99%